The motivational factor of working to involve outdoor sport as mediated by health awareness and social influence: a case study for China and Malaysia - Yan Shao; Lei Wang; Hao Tian Jin; Hao Xuan Ye (BMC Public Health)
Abstract Objectives This study examines the motivating factors influencing outdoor sports participation in China and Malaysia, emphasizing the mediating roles of social influence and health consciousness, and their implications for policy and community engagement. Study design A mixed-methods approach was employed in this cross-sectional study, integrating quantitative surveys and qualitative focus group discussions to capture diverse perspectives on outdoor sports participation and its motivating factors. Methods Data were collected from 500 individuals using self-administered questionnaires assessing motivation, social influence, health awareness, and participation frequency. Statistical analyses, including regression, mediation, and correlation, were conducted to explore the relationships between these variables. Focus group discussions provided additional insights into the motivational factors driving outdoor sports engagement, with particular attention to the role of social influence and community-driven initiatives. Results Findings reveal a significant positive relationship between health awareness and the motivation to engage in outdoor sports. Social influence indirectly affects participation through its impact on health awareness and motivation. Comparative analysis highlights both similarities and differences in these dynamics between China and Malaysia. The study demonstrates the importance of leveraging social networks, community programs, and digital campaigns to foster outdoor sports participation. Conclusions The study underscores the crucial role of social influence and health awareness in shaping outdoor sports participation. These insights inform policy recommendations, advocating for integrated health education programs and community-driven social interventions. Policymakers should focus on fostering community engagement through digital campaigns, public health initiatives, and government-backed programs that use social influence to promote outdoor sports and physical activity, ultimately contributing to improved public health outcomes.